2015
DOI: 10.4103/2231-0762.161756
|View full text |Cite
|
Sign up to set email alerts
|

Orthodontics as a prospective career choice among undergraduate dental students: A prospective study

Abstract: Objectives:The purposes of this study were to investigate the factors influencing the career choice of dental students and to identify the future life plans of the students at Prince Sattam Bin Abdulaziz University Dental College who had chosen orthodontics as their future specialty.Materials and Methods:An epidemiological descriptive survey was conducted using a set of questionnaire among the second year to fourth year students at Prince Sattam Bin Abdulaziz University, Al Kharj, Saudi Arabia. Data were categ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 21 publications
2
9
2
Order By: Relevance
“…[ 30 ] The higher level of overall job satisfaction might be attributed to the fact that 88.2% of the respondents had chosen orthodontics specialty as their first choice. The findings are in agreement with those of Sam,[ 31 ] who reported that 85.1% of the undergraduate students in his study decided to choose orthodontics as their professional career before graduation. Gallagher and Resmi Nairn[ 32 ] from the King's College London Dental Institute also reported orthodontics as the most popular career choice among dental specialties equivalent to restorative dentistry.…”
Section: Discussionsupporting
confidence: 92%
“…[ 30 ] The higher level of overall job satisfaction might be attributed to the fact that 88.2% of the respondents had chosen orthodontics specialty as their first choice. The findings are in agreement with those of Sam,[ 31 ] who reported that 85.1% of the undergraduate students in his study decided to choose orthodontics as their professional career before graduation. Gallagher and Resmi Nairn[ 32 ] from the King's College London Dental Institute also reported orthodontics as the most popular career choice among dental specialties equivalent to restorative dentistry.…”
Section: Discussionsupporting
confidence: 92%
“…Results from earlier studies, showed a wide range of viewpoints (Freire et al, 2011;Dhima et al, 2012;Aggarwal et al, 2012;dos Santos et al, 2013;Knevel et al, 2015;Sam, 2015;Sam et al, 2016;Nassar et al, 2016) related to career choices of Dental students. Generally, studies have indicated that Dental students' career choices are geared towards the students' own gains than towards the roles they are needed to play in their societies (Chattopadhyay & Chatterjee, 1991;Brand & Chikte, 1997;Vigild & Schwarz, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…But, comprehensive data on the future career plans of its products and factors related to the students' career choices is lacking. If it was available, such data could be used by employers to plan human resource for oral health and by academic institutions to establish demand driven post-graduate programs (Sam, 2015). Further, the implication of lacking such information is that, some of the already established postgraduate programs in certain institutions are completely lacking applicants and some receive applicants intermittently.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations